A SIMULATION-BASED FAULT RESILIENCE ANALYSIS FOR REAL-TIME SYSTEMS - Nascimento, Flávia Maristela Santos (2017)
Submitted by Diogo Barreiros (diogo.barreiros@ufba.br) on 2017-02-17T14:47:00Z No. of bitstreams: 1 flavia maristela santos nascimento.pdf: 1166834 bytes, checksum: 576c7c98a85b5cc824a7869fbb31347e (MD5)